Acute presentation of caesarean scar pregnancy at 19 weeks with hemorrhage and anemia: a case of successful surgical intervention - Febriani,; Oktama, Nizan D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Caesarean scar pregnancy (CSP) occurs when an early pregnancy implants on myometrial tissue previously disrupted by a caesarean section (CS). As primary CS rates increase and vaginal deliveries post-CS decrease, CSP has become more prevalent, accounting for 6.1% of all "ectopic" pregnancies. CSP is now recognised as a possible precursor to placenta-accrete spectrum disease (PASD). Unlike tubal ectopic pregnancies, CSP may progress, and successful deliveries have been reported, though no consensus on optimal treatment exists. A 38-year-old G3P2A0 presented at 19 weeks’ gestation with abdominal pain and vaginal bleeding. Ultrasound confirmed a CSP with a 19-week foetus and no heartbeat. Given the low haemoglobin level (7.2 g/dl) and clinical findings, an emergency laparotomy was performed, revealing placenta implantation at the caesarean scar. The foetus had demised, and the patient underwent bilateral pomeroy tubectomy and blood transfusion. CSP management varies, with surgical intervention often required to prevent severe complications. Early diagnosis and a multidisciplinary approach are essential, with treatment decisions guided by residual myometrial thickness (RMT) and the patient's fertility goals. While literature suggests that surgical intervention is generally safer, the optimal treatment approach for CSP remains undetermined, necessitating further research and standardised guidelines.